Analisis Kritik Sosial dalam Novel Max Havelaar Karya Multatuli - Ahmad Zaki; Nabillah Nur Azzizah Muharram (Studi Administrasi Publik dan ilmu Komunikasi, 2024)
Max Havelaar's book (1860) is a novel by Multatuli, a Dutch writer whose real name is Eduard Douwes Dekker. The book written by Multatuli contains criticism of the Dutch colonial government's policy of forced planting and exploitation that afflicted the people of the Dutch East Indies (the name of Indonesia at that time). This research aims to find out how the book describes the social criticism directed at the Dutch colonial government over the forced planting policy during the colonial period. The method used is descriptive analytical with literature study techniques. The object of research is the book Max Havelaar by Multatuli. The results of the analysis show that the social criticism conveyed by Multatuli in Max Havelaar's novel aims to open the awareness of the Dutch colonial government and local nobles about the unfair and unequal government system so as to cause suffering for the indigenous people. This research has the potential to be a reference.